Comparative evaluation of analgesic efficacy of buprenorphine transdermal patch and fentanyl transdermal patch in the management of postoperative pain after lower limb surgery - Qutubuddin, Saifee Sakina; Agarwal, Sangeeta Bansal; Parashar, Deepshikha; Singh, Vijaya Laxmi; Gupta, Garima (International Journal of Basic & Clinical Pharmacology, 2024)
Background: Postoperative pain represents a significant medical issue that needs immediate attention. Despite advancements in pain management, managing postoperative pain remains challenging. Transdermal drug delivery systems (TDDS) offers a straightforward, reliable, non-invasive, and patient-friendly approach for alleviating post-surgical pain. Hence, this study was planned to evaluate the analgesic efficacy of buprenorphine and fentanyl transdermal patch in the management of post-operative pain after lower limb surgery. Methods: In this prospective, randomised study, 82 adult patients of either sex undergoing elective lower limb surgery were randomly allocated into two groups- Group A (Transdermal Buprenorphine 20 mg patch) and Group B (Transdermal Fentanyl 50 mcg patch). Postoperative pain was assessed by 10-point Visual Analogue Scale (VAS) every 6 hours following surgery on the first day and then daily for next 4 days. All patients were also monitored for total rescue analgesic requirement, drug-related adverse effect and haemodynamic status. Statistical analysis was carried out using student t-test and Chi-square test. A p-value <0.05 was considered significant. Results: The mean pain intensity scores were found to be significantly different (p<0.0001) between the two groups, with VAS scores consistently lower in Buprenorphine group as compared to Fentanyl group. Also, Buprenorphine group had the lowest demand for rescue analgesic, with 58.5% of patients requiring two administrations and 36.6% needing only one. Patients belonging to Fentanyl group exhibited higher occurrence of nausea (46.3%), vomiting (46.3%) and pruritus (31.7%). Conclusions: Our study concludes that transdermal patch of buprenorphine demonstrates superior efficacy and safety profile as compared to fentanyl patch for post-operative pain management in lower limb surgeries.